2015
DOI: 10.1016/j.ihj.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Does aortic valve sclerosis predicts the severity and complexity of coronary artery disease?

Abstract: AVS is probably a benign marker of age-related degenerative changes in the heart independent of the severity and complexity of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Previously defined and well-known traditional atherosclerotic risk factors such as advanced age, male sex, HT, DM, and smoking are related to stable CAD rather than ACS, and these risk factors have strong correlations with AVS. In previous studies, it has been demonstrated that AVS and the SS may be related to cardiac mortality and morbidity (2,6,8,9,16,18,19). We also found a strong relation between AVS and the SS and this result supports that AVS is related to the prevalence of CAD and undesired cardiovascular events.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previously defined and well-known traditional atherosclerotic risk factors such as advanced age, male sex, HT, DM, and smoking are related to stable CAD rather than ACS, and these risk factors have strong correlations with AVS. In previous studies, it has been demonstrated that AVS and the SS may be related to cardiac mortality and morbidity (2,6,8,9,16,18,19). We also found a strong relation between AVS and the SS and this result supports that AVS is related to the prevalence of CAD and undesired cardiovascular events.…”
Section: Discussionsupporting
confidence: 87%
“…Many studies showed that there is an important relation between the SS and undesired cardiac outcomes (8,16,17). To date, there are a few studies investigating the relation between the SS and AVS (2,9,15,18). In these studies, ACS cases were included and the relation of the SS with AVS was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 study by Bhatt et al 13 attempted to determine the association between the presence or absence of aortic valve sclerosis and cardiovascular risk factors, CAD extent, and severity of coronary lesions. After allocating 482 patients evaluated with coronary cineangiography into two groups, with and without valvular sclerosis, age was the only independent predictor of aortic valve sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although Bhatt et al 13 found no association between hypercholesterolemia and mitral annular calcification, further studies are needed to determine whether the use of statins would affect prognosis in these patients. Although many patients in the present study used drugs such as ACEIs (65.5% of the patients), aspirin (45.8%), and statin (17.7%), the study was not delineated to correlate the use of drugs and the presence of cardiac calcification.…”
mentioning
confidence: 91%
See 1 more Smart Citation